Impact of a weight loss program on migraine in obese adolescents. Issue 2 (29th May 2012) - Verrotti, A.; Agostinelli, S.; D'Egidio, C.; Di Fonzo, A.; Carotenuto, M.; Parisi, P.; Esposito, M.; Tozzi, E.; Belcastro, V.; Mohn, A.; Battistella, P. A.
<x xml:space="preserve">Abstract</x> Background and purpose Increased headache frequency and severity have been observed in obese populations, but the real impact of a weight loss treatment on headache has not been studied. We investigated this issue in a sample of obese adolescents. Methods In all, 135 migraineurs, aged 14–18 years, with body mass index (BMI) ≥97th percentile, participating in a 12‐month‐long program, were studied before and after treatment. The program included dietary education, specific physical training, and behavioral treatment. Results Decreases in weight (P < 0.01), BMI (P < 0.01), waist circumference (P < 0.01), headache frequency (P < 0.01) and intensity (P < 0.01), use of acute medications (P < 0.05), and disability (P < 0.05) were observed at the end of the first 6‐month period and were maintained through the second 6 months. Both lower baseline BMI and excess change in BMI were significantly associated with better migraine outcomes 12 months after the intervention program. Conclusions Significant improvements in both adiposity and headache data were observed in obese adolescents with migraine who participated in a 12‐month‐long interdisciplinary intervention program for weight loss. Initial body weight and amount of weight loss may be useful for clinicians to predict migraine outcomes.